Analisis Efektivitas Pengadaan Barang/Jasa secara Elektronik (E-Procurement) pada Dinas Tanaman Pangan dan Hortikultura Provinsi Jawa Barat - Hikmah, Rismayanti Nurul; Irjayanti, Maya (Accounting Undergraduate (S1) and Diploma Study Program (D3), STIE EKUITAS, 2022)
This study aims to determine the application of e-procurement in the procurement of goods/services activities and it is relation to the effectiveness of procurement, as well as to identify the success and failure factors of the implementation of e-procurement. The object of research is the procurement of goods/services electronically (e-procurement) in Dinas Tanaman Pangan dan Hortikultura Provinsi Jawa Barat. In this study using a descriptive method with a qualitative approach. Data collection techniques were obtained from primary data in the form of observation, interviews, and documentation. Meanwhile, secondary data was obtained from books, literature, and other published data. The results of this study showed three findings. First, the implementation of e-procurement in the procurement of goods/services in Dinas Tanaman Pangan dan Hortikultura Provinsi Jawa Barat can be said to be going well and is in accordance with applicable regulations related to Government Procurement of Goods/Services. Second, the implementation of goods/services procurement activities electronically (e-procurement) has been effective. This is reflected in the achievement of the five goals that have been set. Third, the success and failure factors of e-procurement are classified based on three crucial factors, namely human factors, technology, and processes. Proposed improvements in the form of socialization, training, and evaluation related to the implementation of e-procurement should be made as an effort to increase the effectiveness of procurement.